If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 73 = f(x) Multiply f * x 73 = fx Solving 73 = fx Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-1fx' to each side of the equation. 73 + -1fx = fx + -1fx Combine like terms: fx + -1fx = 0 73 + -1fx = 0 Add '-73' to each side of the equation. 73 + -73 + -1fx = 0 + -73 Combine like terms: 73 + -73 = 0 0 + -1fx = 0 + -73 -1fx = 0 + -73 Combine like terms: 0 + -73 = -73 -1fx = -73 Divide each side by '-1x'. f = 73x-1 Simplifying f = 73x-1
| 6x+15-2x=-25 | | log(x)2=0 | | 4/7(15.5) | | 2h/3-0.25=.33 | | -2(x+3)+5x=4-2x-5 | | 3.6+m=2 | | Logx(0.5x+4)=0 | | F(x)=73 | | -11=61-6f | | w+5w+9= | | 81-4x=121-6x | | 7k-11= | | -8-3d=25 | | 2(x-8)=x+3-12 | | 10n=240 | | 24.25/.75 | | 13(9c-3)=5c-8 | | 2(2x-21)=360-2(x) | | 2x-3(2+x)=4x+12 | | .6+.33m=.4 | | X/4=8/3? | | 7x+10=5(x-2) | | 15x+159= | | 1.1+inx^2=6 | | 15x^2+102x-72=0 | | F(X)=2x^3-5x^2-x+14F(4) | | 5x-15=30+2x | | 7x-4(2x-9)=50 | | (1/2x)-4=3-(1/3x) | | 23-2x=22 | | 9f+6g-4f-2g+2= | | 16x^2+8x+2=10 |